2020
DOI: 10.1146/annurev-nucl-101918-023530
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Top Quark Mass?

Abstract: This review provides an overview of the conceptual issues regarding interpretation of so-called direct top quark mass measurements, which are based on the kinematic reconstruction of top quark decay products at the Large Hadron Collider (LHC). These measurements quote the top mass parameter m1MCof Monte Carlo event generators with current uncertainties of around 0.5 GeV. The problem of finding a rigorous relation between m1MC and top mass renormalization schemes defined in field theory is unresolved to date an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 154 publications
(124 reference statements)
0
83
0
Order By: Relevance
“…On the other hand, the MSR mass is discussed in various theory papers, mainly focusing on its definition and properties (see e.g. [43][44][45]). As for the top quark case, the main novelties of our work are the phenomenological predictions for NLO differential cross-sections in pp collisions using the MSR mass, which we compare to those with the MS and pole masses in a consistent framework, the implementation of a dynamical mass renor-JHEP04(2021)043 malization scale in the computation of transverse momentum distributions of the heavyquarks, as an alternative to the static m(m) case, and the extraction of a top MSR mass value from the analysis of state-of-the-art LHC triple-differential cross-section data, previously used for extracting m(m) [46].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the MSR mass is discussed in various theory papers, mainly focusing on its definition and properties (see e.g. [43][44][45]). As for the top quark case, the main novelties of our work are the phenomenological predictions for NLO differential cross-sections in pp collisions using the MSR mass, which we compare to those with the MS and pole masses in a consistent framework, the implementation of a dynamical mass renor-JHEP04(2021)043 malization scale in the computation of transverse momentum distributions of the heavyquarks, as an alternative to the static m(m) case, and the extraction of a top MSR mass value from the analysis of state-of-the-art LHC triple-differential cross-section data, previously used for extracting m(m) [46].…”
Section: Introductionmentioning
confidence: 99%
“…2 For δ > 1, i.e. µ < µ thres , we run the couplings using the three-loop SM beta functions, and the central values of the observed strong coupling constant and particle masses [136,137] At the threshold scale, µ = µ thres , we let the couplings λ and y t jump by ∆λ and ∆y t to parametrise the unknown effects of physics around the scale where perturbative unitarity is violated. For simplicity, we omit jumps in the gauge couplings and directly match their SM and chiral SM values at the threshold.…”
Section: Jhep04(2021)059mentioning
confidence: 99%
“…Besides, at future electronpositron colliders the top-quark mass can be measured much more precisely via an energy scan at threshold of top-quark pair production [30]. A recent review on various topics in determination of top-quark mass can be found in [31].…”
Section: Introductionmentioning
confidence: 99%